Fournier’s gangrene mortality: A 17-year systematic review and meta-analysis - Amr Ehab El-Qushayri; Khalid Muhammad Khalaf; Abdullah Dahy; Abdalla Reda Mahmoud; Amira Yasmine Benmelouka; Sherief Ghozy; Mohamed Usama Mahmoud; May Bin-Jumah; Saad Alkahtani; Mohamed M. Abdel-Daim (International Journal of Infectious Diseases, 2020)
Background: To provide better management of Fournier’s gangrene, mortality-associated comorbidities and common etiologies were identified. Methods: A systematic search was conducted using 12 databases, followed by meticulous screening to select relevant articles. Meta-analysis and meta-regression (for possible cofounders) were both done for all possible outcomes. Results: Out of 1186 reports screened, 38 studies were finally included in the systematic review and meta-analysis. A higher risk of mortality was detected in patients with diabetes, heart disease, renal failure, and kidney disease, with risk ratios (RR) and 95% confidence intervals (95% CI) of 0.72 (0.59–0.89), 0.39 (0.24–0.62), 0.41 (0.27–0.63), and 0.34 (95% CI 0.16–0.73), respectively. However, there was no association between mortality rates and comorbid hypertension, lung disease, liver disease, or malignant disease (p > 0.05). The highest mortality rates were due to sepsis (76%) and multiple organ failure (66%), followed by respiratory (19.4%), renal (18%), cardiovascular (15.7%), and hepatic (5%) mortality. Conclusions: Modifications to the Fournier’s Gangrene Severity Index (FGSI) are recommended, in order to include comorbidities as an important prognostic tool for FG mortality. Close monitoring of the patients, with special interest given to the main causes of mortality, is an essential element of the management process. Keywords: Fournier’s gangrene, Mortality, Systematic review